1993
DOI: 10.1007/bf00910492
|View full text |Cite
|
Sign up to set email alerts
|

Narrative abilities in children with attention deficit hyperactivity disorder and normal peers

Abstract: A story retelling task was used to assess narrative abilities in 30 boys with attention deficit hyperactivity disorder (ADHD) and 30 normally developing boys, matched on age and IQ. Each boy listened to two stories and retold them for another child. Results indicated that the two groups did not differ in their ability to comprehend and extract the main ideas from the stories, but did differ in the production of narratives. Boys with ADHD provided less information overall, and their stories were more poorly org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
4
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 24 publications
5
87
4
10
Order By: Relevance
“…Tannock, Purvis, and Schachar [17] Children with ADHD (30 boys aged 7-11 years) versus TD that matched in age and sex.…”
Section: Study Subjects and Age Range Sitting And Procedures Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tannock, Purvis, and Schachar [17] Children with ADHD (30 boys aged 7-11 years) versus TD that matched in age and sex.…”
Section: Study Subjects and Age Range Sitting And Procedures Findingsmentioning
confidence: 99%
“…On the other hand, Tannock et al [17] studied the narrative abilities of children with ADHD (30 boys aged 7-11 years) versus TD, matched in age and sex. Tannock and her colleagues concluded that the participants with ADHD produced significantly fewer units (a unit was defined as one which contained an idea) and less information overall than the TD boys' group, which they counted as evidence of a production deficit in the children with ADHD.…”
Section: Verbal Outputmentioning
confidence: 99%
“…Utilizaron los mismos estímulos que Tannock et al (1993) pero emplearon un modelo de análisis distinto: el análisis de la red causal (Trabasso, Secco y van den Broek, 1.984; Trabasso y van den Broek, 1985). Los resultados que obtuvieron mostraban que, en general, los niños con TDAH presentan déficits tanto en la cantidad de recursos cognitivos que dedican a la comprensión de la historia como en la forma en que distribuyen esos recursos.…”
Section: Amparo Ygual Fernández Ana Miranda Casasunclassified
“…Tannock, Purvis y Schachar (1993) analizaron las habilidades narrativas observando el tipo de errores de producción. Los niños con TDAH cometieron más errores de secuenciación y más errores en la interpretación de la información.…”
Section: Amparo Ygual Fernández Ana Miranda Casasunclassified
“…Tannock, Purvis, and Schachar (1993) Sanchez et al (1999) found no significant differences in recall between the ADHD and comparison groups of children. The study did show that causal structure aided the recall of 4-to 7-year-old children, but had less of an effect on the recall of those with ADHD.…”
Section: Attention and Causal Understandingmentioning
confidence: 98%